The leader in me - Covey, Stephen R. (New York : SIMON & SCHUSTER, 2008)
An introduction to leadership draws on a program developed for an elementary school to show how to apply the principles of The 7 Habits of Highly Effective People to help everyone, including young children, identify their individual talents and find ways to use them in everyday life.
Keywords: Leadership -- Study and teaching (Elementary); Leadership -- Study and teaching -- United States